Implementation of Teqnique Fitting Concept for Pre-Design E-Book Edupark Physics Tourism Object Sasak Beach Pasaman Barat Indonesia - Anjani, Hilmi Rizki; Rifai, Hamdi (Postgraduate, University of Mataram, 2024)
The implementation of the Edupark physics e-book uses a scientific approach to improve environmental literacy skills in accordance with the learning that is expected to be developed to face the industrial revolution 4.0. This research aims to see and analyze eduparks at beach tourist After analysis, this Edupark e attractions and the relationship between physical materials and these tourist attractions. -book can be developed. The results of this study are printed books are still dominantly used in schools, and there is still a lack of use of non-printed books; The average results of students' knowledge and skills are still low, Teaching materials integrated with Edupark at tourist attractions are still rarely used, the effectiveness of using a scientific approach. The conclusion from the results of this research is that there is a need to develop an integrated physics education e-book in tourist destinations.